Patients with non-Jo-1 anti-tRNA-synthetase autoantibodies have worse survival than Jo-1 positive patients. Issue 1 (19th February 2013) - Aggarwal, Rohit; Cassidy, Elaine; Fertig, Noreen; Koontz, Diane Carol; Lucas, Mary; Ascherman, Dana P; Oddis, Chester V
Abstract : Objective: To compare the cumulative survival and event free survival in patients with Jo-1 versus non-Jo-1 anti-tRNA synthetase autoantibodies (anti-synAb). Methods: Anti-synAb positive patients initially evaluated from 1985 to 2009 were included regardless of the connective tissue disease (CTD) diagnosis. Clinical data were extracted from a prospectively collected database and chart review. Survival between Jo-1 and non-Jo-1 was compared by log rank and Cox proportional hazards methods. Results: 202 patients possessed anti-synAb: 122 Jo-1 and 80 non-Jo-1 (35 PL-12; 25 PL-7; 9 EJ; 6 KS; 5 OJ). The diagnoses at first visit for Jo-1 and non-Jo-1 patients were myositis in 83% and 40.0%, overlap or undifferentiated CTD in 17% and 47.5%, and systemic sclerosis in 0% and 12.5%, respectively (p<0.001). The median delay in diagnosis was 0.4 years in Jo-1 patients versus 1.0 year in non-Jo-1 patients (p<0.001). The most common causes of death in the overall cohort were pulmonary fibrosis in 49% and pulmonary hypertension in 11%. The 5- and 10-year unadjusted cumulative survival was 90% and 70% for Jo-1 patients, and 75% and 47% for non-Jo-1 patients (p<0.005). The hazard ratio (HR) of non-Jo-1 patients compared with Jo-1 patients was 1.9 (p=0.01) for cumulative and 1.9 (p=0.008) for event free survival from diagnosis. Age at first diagnosis and diagnosis delay but not gender, ethnicity and CTD diagnosis influenced survival. Conclusions: Non-Jo-1 anti-synAb positive patients have decreased survival compared with Jo-1 patients. The difference in survival may be partly attributable to a delay in diagnosis in the non-Jo-1 patients.